Nitrogen transformations and emission of greenhouse gases from three acid soils of humid tropics amended with N sources and moisture regime. I. Nitrogen transformations - Khalil, M.I.; Cleemput, O. Van; Boeckx, P.; Rosenani, A.B. (Taylor & Francis, 2001)
Laboratory studies were carried out to investigate the nitrogen (N) transformation processes of three Malaysian acid soils (pHH2O ranged from 3.74-4.44) belonging to Aeric Tropic Fluvaquent and Xanthic Hapludox. The soils, amended with inorganic and organic N sources, were incubated at 25°C separately under aerobic and anaerobic conditions. The N mineralization followed zero order kinetics during 15 days of the incubation with a large accumulation of NH+ 4-N under both moisture levels. Addition of sugar beet leaves, having a lower C/N ratio, influenced N mineralization in terms of NH+4 accumulation to a greater extent. Wheat straw, having a wider C/N ratio, limited N mineralization i.e. might induce immobilization of N. Under aerobic conditions, nitrification was either small with NH+4 fertilizer or caused some NO-3 reduction with organic residues and the increased mineralized N with NH+4-fertilizer indicated a priming effect might occur. Under anaerobic conditions, disappearance of NO-3 followed first order kinetics. The disappearance was very rapid supplied with both NO-3-fertilizer and sugar beet leaves. The acidity did not limit intense NO-3 reduction rather showed a predominant accumulation of NH-4-N under anaerobic conditions. Accumulation of NO-2 was low because of the small nitrification or slow NO-3 reduction rate under aerobic conditions. The NO-3 fertilizer and sugar beet leaves increased NO-2 accumulation to several-folds under anaerobic conditions followed by its consumption. The N transformations varied with N sources and moisture regime.